HYDRODYNAMIC MODELS RABOTYAEROTENKA FROM FLOODED AIR-LIFT AERATION SYSTEM - , В. И., В. С. (Municipal economy of cities. Series: «Economy science», 2013)
The question of calculating the aeration tank with air lift submerged aeration system. The theoretical dependence connecting the airflow supplied to the building, with the hydrodynamic liquid flow parameters therein. The graphs for the calculation of the aeration tanks with submerged aeration system.